PBRM1 loss is associated with increased sensitivity to MCL1 and CDK9 inhibition in clear cell renal cancer - Fultang, Norman; Schwab, Ashley M.; McAneny-Droz, Sophia; Grego, Alexander; Rodgers, Stephanie; Torres, Brian Vidal; Heiser, Diane; Scherle, Peggy; Bhagwat, Neha (Frontiers in Oncology, 2024)
MCL1 is a member of the BCL2 family of apoptosis regulators, which play a critical role in promoting cancer survival and drug resistance. We previously described PRT1419, a potent, MCL1 inhibitor with anti-tumor efficacy in various solid and hematologic malignancies. To identify novel biomarkers that predict sensitivity to MCL1 inhibition, we conducted a gene essentiality analysis using gene dependency data generated from CRISPR/Cas9 cell viability screens. We observed that clear cell renal cancer (ccRCC) cell lines with damaging PBRM1 mutations displayed a strong dependency on MCL1. PBRM1 (BAF180), is a chromatin-targeting subunit of mammalian pBAF complexes. PBRM1 is frequently altered in various cancers particularly ccRCC with ~40% of tumors harboring damaging PBRM1 alterations. We observed potent inhibition of tumor growth and induction of apoptosis by PRT1419 in various preclinical models of PBRM1-mutant ccRCC but not PBRM1-WT. Depletion of PBRM1 in PBRM1-WT ccRCC cell lines induced sensitivity to PRT1419. Mechanistically, PBRM1 depletion coincided with increased expression of pro-apoptotic factors, priming cells for caspase-mediated apoptosis following MCL1 inhibition. Increased MCL1 activity has been described as a resistance mechanism to Sunitinib and Everolimus, two approved agents for ccRCC. PRT1419 synergized with both agents to potently inhibit tumor growth in PBRM1-loss ccRCC. PRT2527, a potent CDK9 inhibitor which depletes MCL1, was similarly efficacious in monotherapy and in combination with Sunitinib in PBRM1-loss cells. Taken together, these findings suggest PBRM1 loss is associated with MCL1i sensitivity in ccRCC and provide rationale for the evaluation of PRT1419 and PRT2527 for the treatment for PBRM1-deficient ccRCC.